The practice and procedure of the Human Rights Committee under the International Covenant on Civil and Political Rights - McGoldrick, Dominic (1988)
This thesis examines the practices and procedures of the Human Rights Committee, the body established under the International Covenant On Civil And Political Rights (ICCPR) (1966).